2012
DOI: 10.1186/1472-6882-12-225
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of spinal orexin A in the electroacupuncture analgesia in a rat model of post-laparotomy pain

Abstract: BackgroundOrexin A (OXA, hypocretin/hcrt 1) is a newly discovered potential analgesic substance. However, whether OXA is involved in acupuncture analgesia remains unknown. The present study was designed to investigate the involvement of spinal OXA in electroacupuncture (EA) analgesia.MethodsA modified rat model of post-laparotomy pain was adopted and evaluated. Von Frey filaments were used to measure mechanical allodynia of the hind paw and abdomen. EA at 2/15 Hz or 2/100 Hz was performed once on the bilateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 51 publications
2
33
1
Order By: Relevance
“…A recent study using a rat model reported a significant increase of orexin A following electroacupuncture therapy after a laparotomy. 25 In contrast, our results did not show a statistically significant change in orexin A levels after a thoracic or cervical SM.…”
Section: Discussioncontrasting
confidence: 56%
“…A recent study using a rat model reported a significant increase of orexin A following electroacupuncture therapy after a laparotomy. 25 In contrast, our results did not show a statistically significant change in orexin A levels after a thoracic or cervical SM.…”
Section: Discussioncontrasting
confidence: 56%
“…23 Animal and human data also support a role for orexins in pain processing. 20 In rat pain models, intrathecally administered OXA has anti-hyperalgesic properties, [24][25][26][27][28] and the specificity of OXA's anti-hyperalgesic effect has been demonstrated by its inhibition when pretreated with the orexin receptor antagonist. 25,29 Additionally, in humans, OXA levels have been shown to be elevated in the cerebrospinal fluid of chronic daily headache sufferers.…”
mentioning
confidence: 99%
“…20 In rat pain models, intrathecally administered OXA has anti-hyperalgesic properties, [24][25][26][27][28] and the specificity of OXA's anti-hyperalgesic effect has been demonstrated by its inhibition when pretreated with the orexin receptor antagonist. 25,29 Additionally, in humans, OXA levels have been shown to be elevated in the cerebrospinal fluid of chronic daily headache sufferers. 30 The findings of OXA's antihyperalgesic properties in animal models and the elevated OXA levels in those with chronic daily headache may suggest orexin resistance or disruptions in orexin receptors in those with chronic headache (which explains the continued pain while having elevated OXA levels).…”
mentioning
confidence: 99%
“…RVLM orexin-A level was quantified with a standard ELISA kit (EK-003–30; Phoenix Pharmaceutical, Burlingame, CA) in accordance with the manufacturer’s procedures and as reported (Feng et al, 2007, 2012; Olszanecka-Glinianowicz et al, 2007). Briefly, four groups of animals treated as described under experimental design were euthanized 10–15 min after WIN55,212-2 or vehicle injection; brains were removed, flash frozen in 2-methylbutane (cooled on dry ice for at least 30 min), and stored at −80 °C until use.…”
Section: Methodsmentioning
confidence: 99%